Catalytic pyrolysis of amino acids: Comparison of aliphatic amino acid and cyclic amino acid. (15th March 2016) - Liu, Guangyi; Wright, Mark M.; Zhao, Qingliang; Brown, Robert C.; Wang, Kaige; Xue, Yuan
Graphical abstract: Highlights: Catalytic pyrolysis of leucine and proline were carried out in a micro-furnace pyrolyzer. Distributions of carbon, oxygen and nitrogen were comparatively investigated. Leucine yielded 29.6% aromatic hydrocarbons, 34.9% olefins, and 8.1% alkanes. Proline yielded 25.3% aromatic hydrocarbons, 14.0% olefins, and 5.5% alkanes. Insights into the deoxygenation pathways of leucine and proline were elucidated. Abstract: Catalytic pyrolysis (CP) of protein-rich biomass such as microalgae is a promising approach to biofuel production. CP of amino acids can help understand the cracking of protein-rich biomass in the presence of zeolite catalysts. In this study, as representatives of aliphatic amino acid and cyclic amino acid, respectively, leucine and proline were pyrolyzed with ZSM-5 catalyst in a Tandem micro-furnace reactor coupled with a MS/FID/TCD. At 650 °C, leucine produced more hydrocarbons (aromatic hydrocarbons of 29.6%, olefins of 34.9% and alkanes of 8.1%) than proline (aromatic hydrocarbons of 25.3%, olefins of 14.0% and alkanes of 5.5%) because its relatively simpler amino structure readily detached as ammonia during CP. However, with an N-cyclic structure, proline produced large quantities of nitrogen-containing heterocyclic compounds that favored coke formation in CP. Accordingly, 28.2% of the nitrogen in proline was retained in the solid residue while most of the nitrogen in leucine was converted into ammonia leaving only 4.3% in the solid residue. In addition, though decarboxylation to carbon dioxide was favored in non-catalytic pyrolysis of leucine and proline, decarbonylation to carbon monoxide became the primary deoxygenation pathway in CP. These results indicate that the chemical structures of amino acids have significant effects on product distributions during CP and N-cyclic amino acid is less favored in CP for production of hydrocarbons and ammonia.